2018
DOI: 10.1371/journal.pone.0191117
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with taste and smell alterations—A qualitative interview study of people treated for lung cancer

Abstract: Taste and smell alterations have been recognized as common symptoms in relation to various cancers. However, previous research suggests that patients do not receive sufficient support in managing taste and smell alterations. Therefore, the objective of this study is to investigate how persons with experience from lung cancer-related taste and smell alterations reason about resources and strategies offered and used to manage these symptoms. Data from semi-structured individual interviews with 13 women and four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 33 publications
1
25
0
3
Order By: Relevance
“…Compared with those with breast cancer, patients with lung cancer had a lower risk of being in the CFT group. While previous studies reported altered taste perceptions in patients with breast, 4,20,25,44 lung, 45,46 and gynecological 25,47 cancers, no studies were identified that examined relative risk of CFT across cancer diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with those with breast cancer, patients with lung cancer had a lower risk of being in the CFT group. While previous studies reported altered taste perceptions in patients with breast, 4,20,25,44 lung, 45,46 and gynecological 25,47 cancers, no studies were identified that examined relative risk of CFT across cancer diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported how patients find ways to avoid unpleasant taste or smell experiences or manage the social impact of TSCs [ 43 ]. Based on patients' understanding of the TSCs, proactive patients with a positive attitude will take the initiative to manage their eating habits, such as eating healthier (less fat, more vegetables), choosing seasonings to adjust the taste of food, avoid odor, to name a few [ 44 ]. Therefore, FC and IBS patients need to be aware of the potential changes in their taste and smell to be able to manage their eating habits.…”
Section: Discussionmentioning
confidence: 99%
“…This article mainly included information about pharmacological treatment (antiemetics) and cited few non‐pharmacological intervention studies, although the authors stated that such interventions play an important role and should therefore also be addressed in future studies. Taste and smell disorders are troublesome conditions for cancer patients (Belqaid, Tishelman, Orrevall, Mansson‐Brahme, & Bernhardson, 2018). No RCT addressing this important topic in HSCT patients was identified, although the prevalence of these disorders can reach up to nearly 80% in cancer patients undergoing chemotherapy and such disorders increase the risk of malnutrition (Amezaga et al., 2018; Cohen, Wakefield, & Laing, 2016; Okada et al., 2016).…”
Section: Discussionmentioning
confidence: 99%